Tobacco susceptibility among junior high school students in the Upper East Region, Ghana - Divine Darlington Logo; Prakash Babu Kodali; Padmini Bisoyi; Judith Anaman-Torgbor; Benjamin W. Chaffee; Stella A. Bialous; Ellis Owusu-Dabo (Discover Public Health, 2026)
Abstract Background The rising use of tobacco among adolescents is a significant public health challenge. Understanding susceptibility to tobacco use is crucial for effective prevention. This study determined the prevalence and correlates of tobacco use susceptibility among junior high school adolescents in the Upper East Region of Ghana. Methods We conducted a cross-sectional analysis using baseline data from a school-based tobacco prevention program in Ghana ( N = 1015 adolescents who never tried tobacco) in 2022. A multistage cluster sampling approach facilitated data collection using self-administered questionnaires, which captured individual, social, and environmental factors related to tobacco susceptibility. Tobacco susceptibility was assessed using a 5-item Likert-type scale, dichotomized for analysis. We computed unadjusted and adjusted odds ratios (AORs) with 95% confidence intervals using multivariable binary logistic regression to identify factors associated with tobacco susceptibility. Results Overall, 17.5% of adolescents showed susceptibility to tobacco use, with a higher prevalence observed in lower grades (21.1% in Grade 1) and among the Bulsa ethnicity (20.4%). Individual characteristics, such as no religion, significantly increased the odds of high susceptibility (AOR = 2.0, 95%CI = 1.3-3.0) compared to Christians. Environmental factors, specifically working on tobacco farms, also increased the odds of susceptibility (AOR = 2.2, 95% CI = 1.3–3.5). Social influences, such as being asked to light a cigarette (AOR = 2.0, 95%CI = 1.2–3.2), were associated with increased odds of tobacco use susceptibility. Conclusion Nearly one in five adolescents in the Upper East region of Ghana showed susceptibility to future tobacco use. Having no religion, working in tobacco farms, and being exposed to tobacco-related errands were associated with higher susceptibility. These findings can inform focused interventions to prevent tobacco use initiation among adolescent in region.